HIV-1 DNA Testing in Viremic Patients Identifies More Drug Resistance Than HIV-1 RNA Testing. (22nd March 2023) - Curanovic, Dusica; Martens, Sharon K; Rodriguez, Milka A; Hammill, Hunter A; Petropoulos, Christos J; Walworth, Charles M
Abstract: Background: The Department of Health and Human Services HIV-1 Treatment Guidelines recommend drug resistance testing in HIV-1 RNA to guide the selection of antiretroviral therapy in patients with viremia. However, resistance-associated mutations (RAMs) in HIV-1 RNA may reflect only the patient's current regimen and can be lost during prolonged absence of therapy. We determined if HIV-1 DNA testing can provide drug resistance information beyond that identified in contemporaneous plasma virus. Methods: This was a retrospective database review of results obtained for patients with viremia for whom commercial HIV-1 RNA and HIV-1 DNA drug resistance testing was ordered on the same day. Resistance-associated mutations and drug susceptibility calls were compared between paired tests, and the effect of HIV-1 viral load (VL) on test concordance was assessed using Spearmen's rho correlation. Results: Among 124 paired tests, more RAMs were identified in HIV-1 DNA in 63 (50.8%) cases, and in HIV-1 RNA in 11 (8.87%) cases. HIV-1 DNA testing captured all contemporaneous plasma virus RAMs in 101/117 (86.3%) cases and identified additional RAMs in 63/117 (53.8%) cases. There was a significant positive correlation between the viral load at the time of resistance testing and the percentage of plasma virus RAMs detected in HIV-1 DNA (rs = 0.317; P < .001). In 67 test pairs demonstrating pan-sensitive plasma virus, resistance in HIV-1 DNA was seen in 13 (19.4%) cases. Conclusions: HIV-1 DNA testing identified more resistance than HIV-1 RNA testing in most patients with viremia and may be informative in patients whose plasma virus reverts to wild-type following therapy discontinuation. Abstract : In patients with HIV-1 viremia, plasma RNA resistance testing identifies mutations which are mostly reflective of the patient's current failing regimen. Contemporaneous proviral HIV-1 DNA resistance testing may identify additional resistance mutations not seen in the plasma viral compartment.